2015
DOI: 10.5897/sre2015.6322
|View full text |Cite
|
Sign up to set email alerts
|

Photoplethysmogram second derivative review: Analysis and applications

Abstract: Photoplethysmogram (PPG) and its second derivative of the photoplethysmogram (SDPTG) are simple and low cost optical techniques for detecting and tracking blood volume changes. The PPG waveform and its SDPTG have been used by many scholars to obtain valuable information about heart and cardiovascular system. Since PPG and SDPTG reflect blood volume changes, much work has been done on its application as a diagnostic tool for screening arterial structure and its related diseases and disorders. In this article, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…PPG signal is used in this study to extract some morphological indices that may be used for diabetes prediction. PPG waveform can be explained as a volumetric measure for blood volume changes inside arteries [7,8]. Still, there is no unified definition for the origin of PPG signal, but it can be understood as an optical plethysmograph [9].…”
Section: Introductionmentioning
confidence: 99%
“…PPG signal is used in this study to extract some morphological indices that may be used for diabetes prediction. PPG waveform can be explained as a volumetric measure for blood volume changes inside arteries [7,8]. Still, there is no unified definition for the origin of PPG signal, but it can be understood as an optical plethysmograph [9].…”
Section: Introductionmentioning
confidence: 99%
“…As described in previous studies, the AI obtained by dividing the sum of the c- and d-waves by the a-wave is the blood transition capacity of the peripheral vascular system [ 21 ]. The c-wave is high and the d-wave is low when the blood flow is appropriate (which is observed in the young adults), and the c-wave is low when the blood circulation is poor (as observed in the elderly).…”
Section: Discussionmentioning
confidence: 99%
“…The b/a index is important parameter in the diagnosis of the state of the arterial wall [2]. [15,[22][23][24] demonstrated that the value of b/a index is associated with atherosclerosis and aging.…”
Section: The B/a Indexmentioning
confidence: 99%
“…The evaluation of cutaneous circulation using PPG has been utilized by [14]. The second derivative of PPG signal (SDPTG) has been studied by several researchers seeking valuable information about cardiovascular system activities [15]. The analysis of PPG's derivatives facilitates the process of peaks and valleys detection on the original contour of PPG waveform.…”
Section: Introductionmentioning
confidence: 99%